Optimization of EDF pump for efficient brillouin/ erbium fiber ring laser operation - Saharudin, Suhairi; Abdullah, M. Khazani (2002)
We report here experimental results on the finding of an optimum Erbium pump power in obtaining a Brillouin-generated Stokes signal with the best quality. The quality of the Stokes signal is mainly characterized by its isolation from unwanted modes and noises. We also propose here a new parameter to characterize the signal further that is by using peak power-isolation product. With this particular system, we obtained an optimum Erbium pump power of 48.93 miliwatt producing a peak power 2.91 mW and isolation of 17.6 dB or a peak power-isolation product of 51.23 dB-dBm.